Partisipasi Masyarakat dalam Pengembangan Obyek Pariwisata Ke'te Kesu’ - Ekaprativi, Alifaturrizqi Swari; Arfan, Amal; Abbas, Ibrahim (LaGeografia, 2021)
This study aims to determine community participation in the development of Ke'te Kesu tourism objects in Panta'nakan Lolo Village, Kesu District, North Toraja Regency and the factors that influence community participation in the development of Ke'te Kesu tourism objects in Panta'nakan Lolo Village, Kesu District. North Toraja Regency. This type of research is descriptive qualitative. The data analysis technique used is the data analysis technique in the field with several stages, namely data collection, data reduction, data presentation and then drawing conclusions. The data collection techniques used were observation, interview and documentation. The informants in this study were the managers of the Ke'te Kesu tourism object and the community around the Ke'te Kesu tourist attraction with a total of 7 people. Based on the results of research, the local community is very involved in the development of the Ke'te Kesu tourist attraction by giving contributions of energy and ideas, seen from actively maintaining the cleanliness and preservation of the Ke'te Kesu tourist attraction and providing evaluation to the manager. Ke'te Kesu tourism object has a big influence on the surrounding community.